Basement membrane degeneration is common in lichenoid mucositis with dysplasia - Lin, Iris (Can J Dent Hyg, 2021)
BACKGROUND: Two subtypes of lichenoid mucositis (LM) with oral epithelial dysplasia have been proposed, with differing risks of malignant transformation. However, no research has been done to authenticate this hypothesis. The study objective was to determine whether there are 2 subcategories within this entity, one with primary lichenoid and secondary dysplastic features (L(1)D(2)), and the other with primary dysplastic and secondary lichenoid features (D(1)L(2)), and to compare the proportion of malignant progression in these groups. METHODS: Patients with a diagnosis of lichenoid mucositis with low-grade (mild/moderate) oral epithelial dysplasia, no history of head and neck cancer, and who had at least 5 years of follow-up were eligible to participate in this nested case–control study. Cases (n = 10) were defined as lesions that progressed to severe dysplasia, carcinoma in situ or squamous cell carcinoma; controls (n = 32) were defined as those that did not progress. Immunohistochemistry was performed to assess for basement membrane (BM) degeneration using collagen IV—an integral BM protein. RESULTS: Lesions that progressed to cancer exhibited a similar proportion of BM degeneration at baseline (70%) compared to non-progressors (78%), with no statistically significant difference between groups (p = 0.69). CONCLUSION: BM degeneration is frequently seen in LM with dysplasia and alone does not appear to be a predictor of malignant progression in lesions with both lichenoid and low-grade dysplastic features. Dysplasia should not be discounted in the presence of LM. Lesions that display any degree of dysplasia warrant clinical follow-up and continued monitoring.